Transfer of nuclear technology under international law : case study of Iraq, Iran and Israel - Negm, Namira (Martinus Nijhoff Publishers, 2009)
Based on the legal regime governing the transfer of nuclear technology, this book offers a comprehensive overview to both the theoretical and practical aspects of such regime and presents a new perspective to the Middle East nuclear dilemma.